Intensive care for layers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Mr. Wainaina, who keeps over 5000 layers, explains the management systems he uses on his farm in Moisbridge, Kenya.